Pengaruh Pengeluaran Pemerintah Sektor Pertanian dan Investasi terhadap Tenaga Kerja, Pertumbuhan Ekonomi dan Pendapatan Asli Daerah Kabupaten Luwu - Andi M. Iswan Adhiputra Pangerang; Wilda Fatmala; Filasti Rahma; Yunarsi Yunarsi; Husriah Husriah (Jurnal Ekonomi & Bisnis, 2022)
The large budget allocation and agricultural area of luwu county is expected to create jobs for the people of luwu district and attract investors. The deployment of the large budget and the extent of the development of the research is aimed at (1) reviewing and analyzing the impact of government spending on the agricultural sector on luwu's native incomes indirectly through agricultural sector labor and economic growth; And (2) review and analyze the impact of private investment on luwu county's local revenue and indirectly through agricultural sector labor and economic growth. The study used a secondary type of the time serries during the 2004 to 2013 (10 years) collected by the files.The government expenditure in luwu district's agricultural sector and the gross domestic product data on the basis of the 2000 luwu district's constant price. The research makes real incomes independent variables, government spending and investment as dependent variables and labor and economic growth as intering variables. To answer the purpose of the study is done analysis using simultaneous equation model. The results of the data processing in this study suggest that government spending on agriculture was indirectly significant to the local revenue Luwu district. In addition, the research also suggests that investments both directly and indirectly give significant impact to the original income in luwu district.